Tackling Coffee Berry Borer (Hypothenemus hampei Ferr.) Challenges: The Science of Ant Colonization, Nest Design, and Food Preferences in Indonesian Coffee Agroecosystems - Kurnianto, Agung Sih; Haryadi, Nanang Tri; Dewi, Nilasari; Noviardhana, Astiningtia; Puspitasari, Dea Ayu; Laili, Fadlul; Paramita, Sofia Dwi; Magvira, Nur Laila; Handoko, Rose Novita Sari (AGRIVITA Journal of Agricultural Science, 2024)
The black ant (Dolichoderus thoracicus) is known as a natural enemy of Hypothenemus hampei Ferr., the Coffee Berry Borer (CBB). The conservation efforts for this natural enemy can be carried out by using ant nest technology with artificial feed. This research explored artificial nesting and feeding methods for black ant colonies in coffee plantations in Jember District, Indonesia, to combat the CBB. Utilizing a Randomized Block Design, the study examines different nest materials and shapes, various artificial feeds, and the influence of environmental factors on ant colony growth. Cocoa leaves are the most effective nesting material, significantly increasing ant populations (11,532 individuals on average) compared to coconut leaves (4,645.83 individuals); no significant impact of nest shape on ant attraction; granulated sugar is the preferred artificial feed. A notable increase in ant populations was observed with a longer nest placement duration of four weeks. Environmental factors, especially humidity and temperature, significantly influence nests' and feed interactions. The study highlights the importance of specific nesting materials and environmental considerations in effective pest management strategies in tropical agriculture, offering a sustainable approach to enhancing coffee plantation productivity.